Financial accounting fundamentals - Wild, John J. (McGraw-Hill/Irwin, 2007)
Wild’s Financial Accounting Fundamentals responds to the market’s request for a low-cost, succinct book; a book that balances large and small businesses, and one that is contemporary, engaging, and accessible for today’s students. With numerous innovative features, the author focuses on “Three C’s”: Clear presentation of accounting concepts, Concise coverage to help students focus on important material, and Cutting edge technology to engage students and improve their chances for success. The author provides examples from a balance of different size businesses, integration of new computerized learning tools, superior end-of-chapter materials, and highly engaging pedagogical learning structures. Technology tools such as McGraw-Hill's Homework Manager and Carol Yacht’s General Ledger and Peachtree software provides students with further advantages as they learn and apply key accounting concepts and methods.